A novel analytical ultracentrifugation based approach to the low resolution structure of gum arabic - Gillis, Richard B.; Adams, Gary G.; Alzahrani, Qushmua; Harding, Stephen E.; Allen Bush, C. (Wiley, 2016)
Under investigation are the structural properties of gum arabic, an industrially important biopolymer for use as a stabilizer or in drug delivery, using Analytical Ultracentrifugation—a well-established, matrix-free probe for macromolecular size and shape. These results are combined with chromatographically-coupled methods (multi-angle light scattering, differential press imbalance viscometry) to provide a global analysis of its structure in varying ionic strength conditions. This analysis indicates that gum Arabic may have a compact, elliptical structure in solution, the significance of which for biotechnological use is indicated. This modelling method can be applied to other biopolymers and synthetic polymers.